ANALYSIS METHOD OF AUTOMATIC PLANETARY TRANSMISSION KINEMATICS - Józef DREWNIAK; Stanisław ZAWIŚLAK; Andrzej WIECZOREK (Scientific Journal of Silesian University of Technology. Series Transport)
In the present paper, planetary automatic transmission is modeled by means of contour graphs. The goals of modeling could be versatile: ratio calculating via algorithmic equation generation, analysis of velocity and accelerations. The exemplary gears running are analyzed, several drives/gears are consecutively taken into account discussing functional schemes, assigned contour graphs and generated system of equations and their solutions. The advantages of the method are: algorithmic approach, general approach where particular drives are cases of the generally created model. Moreover, the method allows for further analyzes and synthesis tasks e.g. checking isomorphism of design solutions.